A Novel Case of Bifacial Diplegia Variant of Guillain-Barré Syndrome Following Janssen COVID-19 Vaccination - Apoorv Prasad; Gage Hurlburt; Sanjiti Podury; Medha Tandon; Seth Kingree; Shitiz Sriwastava (MDPI AG, 2021)
Guillain-Barré syndrome (GBS) is an immune-mediated demyelinating disorder which attacks the peripheral nervous system. Antecedent infection or vaccine administration are known to precipitate the onset of this disorder. Its typical presentation leads to a symmetric, rapidly progressive, ascending paresis with associated sensory deficits and impaired reflexes. We present a rare case of a bi-facial diplegia variant of GBS, within four weeks of the COVID-19 vaccination. Due to its chronology, clinical manifestations, and cerebrospinal fluid (CSF) findings, we propose this case to be a rare complication of the COVID-19 vaccination.